Strong near band-edge excited second-harmonic generation from multilayer 2H Tin diselenide - Rabindra Biswas (Nature Portfolio, 2021)
Abstract We report strong second-harmonic generation (SHG) from 2H polytype of multilayer Tin diselenide (SnSe2) for fundamental excitation close to the indirect band-edge in the absence of excitonic resonances. Comparison of SHG and Raman spectra from exfoliated SnSe2 flakes of different polytypes shows strong (negligible) SHG and Raman Eg mode at 109 cm−1 (119 cm−1), consistent with 2H (1T) polytypes. The difference between the A1g–Eg Raman peak positions is found to exhibit significant thickness dependent for the 1T form, which is found to be absent for the 2H form. The observed thickness dependence of SHG with rapid oscillations in signal strength for small changes in flake thickness are in good agreement with a nonlinear wave propagation model considering nonlinear polarization with alternating sign from each monolayer. The nonlinear optical susceptibility extracted from SHG signal comparison with standard quartz samples for 1040 nm excitation is found to be more than 4-times higher than that at 1550 nm. This enhanced nonlinear response at 1040 nm is attributed to the enhanced nonlinear optical response for fundamental excitation close to the indirect band-edge. We also study SHG from heterostructures of monolayer MoS2/multilayer SnSe2 which allows us to unambiguously compare the nonlinear optical response of SnSe2 with MoS2. We find the SHG signal and any interference effect in the overlap region to be dominated by the SnSe2 layer for the excitation wavelengths considered. The comparison of SHG from SnSe2 and MoS2 underscores that the choice of the 2D material for a particular nonlinear optical application is contextual on the wavelength range of interest and its optical properties at those wavelengths. The present works further highlights the usefulness of near band-edge enhancement of nonlinear processes in emerging 2D materials towards realizing useful nanophotonic devices.